A combined transcriptomic and physiological approach to understanding the adaptive mechanisms to cope with oxidative stress in Fusarium graminearum - Jiyeun Park; Hyun-Hee Lee; Heeji Moon; Nahyun Lee; Sieun Kim; Jung-Eun Kim; Yoonji Lee; Kyunghun Min; Hun Kim; Gyung Ja Choi; Yin-Won Lee; Young-Su Seo; et al. (Microbiology Spectrum, 2023)
ABSTRACT In plant-pathogen interactions, oxidative bursts are crucial for plants to defend themselves against pathogen infections. Rapid production and accumulation of reactive oxygen species kill pathogens directly and cause local cell death, preventing pathogens from spreading to adjacent cells. Meanwhile, the pathogens have developed several mechanisms to tolerate oxidative stress and successfully colonize plant tissues. In this study, we investigated the mechanisms responsible for resistance to oxidative stress by analyzing the transcriptomes of six oxidative stress-sensitive strains of the plant pathogenic fungus Fusarium graminearum. Weighted gene co-expression network analysis identified several pathways related to oxidative stress responses, including the DNA repair system, autophagy, and ubiquitin-mediated proteolysis. We also identified hub genes with high intramodular connectivity in key modules and generated deletion or conditional suppression mutants. Phenotypic characterization of those mutants showed that the deletion of FgHGG4, FgHGG10, and FgHGG13 caused sensitivity to oxidative stress, and further investigation on those genes revealed that transcriptional elongation and DNA damage responses play roles in oxidative stress response and pathogenicity. The suppression of FgHGL7 also led to hypersensitivity to oxidative stress, and we demonstrated that FgHGL7 plays a crucial role in heme biosynthesis and is essential for peroxidase activity. This study increases the understanding of the adaptive mechanisms to cope with oxidative stress in plant pathogenic fungi. IMPORTANCE Fungal pathogens have evolved various mechanisms to overcome host-derived stresses for successful infection. Oxidative stress is a representative defense system induced by the host plant, and fungi have complex response systems to cope with it. Fusarium graminearum is one of the devastating plant pathogenic fungi, and understanding its pathosystem is crucial for disease control. In this study, we investigated adaptive mechanisms for coping with oxidative stress at the transcriptome level using oxidative stress-sensitive strains. In addition, by introducing genetic modification technique such as CRISPR-Cas9 and the conditional gene expression system, we identified pathways/genes required for resistance to oxidative stress and also for virulence. Overall, this study advances the understanding of the oxidative stress response and related mechanisms in plant pathogenic fungi.